The relationship between physical activity levels and serum vitamin D levels varies among children and adolescents in different age groups - Ouyang, Shengrong; Li, Qin; Liu, Zhuo; Yin, Yan (Frontiers in Nutrition, 2024)
The objective of the present study was to explore the relationship between physical activity (PA) levels and serum vitamin D levels in children and adolescents of different ages and sexes.All the data in this study were collected during two cycles (2011-2014) of the National Health and Nutrition Examination Survey (NHANES). Our study participants were aged ≥ 3 and <20 years and had valid data for all variables, including vitamin D intake, serum vitamin D levels, PA volume and intensity levels, amount of time spent outdoors, body mass index (BMI), sex, and race. Results A total of 3312 participants were included in the study; 1672 were boys (50.4%), and 1640 were girls (49.6%). A total of 250 (7.5%) children were aged 3-5 years, 1474 (44.5%) were aged 6-11 years, and 1588 (47.9%) were aged 12-19 years. Both PA volume and intensity were positively related to serum vitamin D levels in the 6-to 11-year-old boys and girls (p<0.05 for both) and in the 12-to 19-year-old boys. No significant relationship between PA volume or intensity and serum vitamin D levels was detected in the 3-to 5-year-old group or in the 12-to 19-year-old girl group. The time spent outdoors and the BMI of the participants had mediating effects on the relationships of PA volume and intensity with serum vitamin D levels in boys and girls aged 6-11 years. Conclusions The relationship between PA and vitamin D varies among children and adolescents of different sexes and ages, and the sun exposure level and BMI had mediating effects on the relationship between PA and the serum vitamin D level. The mechanism of the relationship between PA and increased serum vitamin D levels needs further in-depth research.